Prognostic significance of plaque location in non-obstructive coronary artery disease: from the CONFIRM registry . (15th November 2021) - Han, Donghee; Chen, Billy; Gransar, Heidi; Achenbach, Stephan; Al-Mallah, Mouaz H; Budoff, Matthew J; Cademartiri, Filippo; Maffei, Erica; Callister, Tracy Q; Chinnaiyan, Kavitha; Chow, Benjamin J W; DeLago, Augustin; et al.
Abstract: Aim: Obstructive coronary artery disease (CAD) in proximal coronary segments is associated with a poor prognosis. However, the relative importance of plaque location regarding the risk for major adverse cardiovascular events (MACE) in patients with non-obstructive CAD has not been well defined. Methods and results: From the Coronary CT Angiography Evaluation for Clinical Outcomes: An International Multicenter (CONFIRM) registry, 4644 patients without obstructive CAD were included in this study. The degree of stenosis was classified as 0 (no) and 1–49% (non-obstructive). Proximal involvement was defined as any plaque present in the left main or the proximal segment of the left anterior descending artery, left circumflex artery, and right coronary artery. Extensive CAD was defined as segment involvement score of >4. During a median follow-up of 5.2 years (interquartile range 4.1–6.0), 340 (7.3%) MACE occurred. Within the non-obstructive CAD group ( n = 2065), proximal involvement was observed in 1767 (85.6%) cases. When compared to non-obstructive CAD patients without proximal involvement, those with proximal involvement had an increased MACE risk (log-rank P = 0.033). Multivariate Cox analysis showed when compared to patients with no CAD, proximal non-obstructive CAD was associated with increased MACE risk [hazard ratio (HR) 1.90, 95% confidence interval (CI) 1.47–2.45, P < 0.001] after adjusting for extensive CAD and conventional cardiovascular risk factors; however, non-proximal non-obstructive CAD did not increase MACE risk (HR 1.26, 95% CI 0.79–2.01, P = 0.339). Conclusions: Independent of plaque extent, proximal coronary involvement was associated with increased MACE risk in patients with non-obstructive CAD. The plaque location information by coronary computed tomography angiography may provide additional risk prediction over CAD extent in patients with non-obstructive CAD. Graphical Abstract: